Androgyny and atypical sensory sensitivity associated with savant ability: a comparison between Klinefelter syndrome and sexual minorities assigned male at birth - Tawata, Shintaro; Sakaguchi, Kikue; Saito, Atsuko (Frontiers in Child and Adolescent Psychiatry, 2024)
Introduction The extreme male brain (EMB) theory, a major causal hypothesis of autism (ASD: autism spectrum disorder), attributes excess androgens during early development as one of the causes. While studies have generally followed the EMB theory in females at birth, the co-occurrence of ASD in males at birth has been observed in conditions that are assumed to be associated with reduced androgen action during early development, including Klinefelter syndrome (KS) and sexual minorities. ASD is also associated with atypical sensory sensitivity, synesthesia, and savant syndrome. Methods In the present study, we examined adult KS individuals (n = 22), sexual minorities assigned male at birth (n = 66), and control males matched for age and educational background to those with KS [Exploratory analysis (control 1st): n = 36; Reanalysis (control 2nd): n = 583]. Participants completed a self-report questionnaire assessing sensory hypersensitivity/hyposensitivity, savant tendency (developed for the present study), synesthesia, and sexual aspects, including gender identity and sexual orientation. Results The results of the exploratory analysis suggested that individuals with KS exhibited a higher tendency toward sensory hypersensitivity/hyposensitivity than the tendency exhibited by the controls. In the Reanalysis, sexual minorities were more likely to be synesthetes, and in both analyses sexual minorities exhibited a higher savant tendency and sensory hypersensitivity/hyposensitivity than the controls. Moreover, the gender dysphoric state was associated with phenotypes observed in individuals with ASD, such as synesthesia, savant tendency, and sensory hypersensitivity/hyposensitivity. Discussion These results suggest a common physiological background among gender dysphoria, synesthesia, savant tendency, and atypical sensory sensitivity. Thus, androgynous features (reduced effects of sex steroids during early development) in males at birth may be partially related to the phenotype commonly observed in individuals with ASD. Based on the present results, we propose that the reduction of sex steroids during early development may lead to atypical neurodevelopment and be involved in the atypicality of external and internal sensory perception, and thus in the atypicality of self-concept integration, through the disruption of oxytocin and the gamma-aminobutyric acid system modulating the neural excitation/inhibition balance.